The mechanism of X80 steel weld microstructure and mechanical properties optimization by induction heating technology - Shichao Zhang; Fulai Yang; Cuicui Chen; Zehua Niu; Yongbin Que; Haidong Jia; Lianshuang Dai; Zheng Zhang (Journal of Materials Research and Technology)
Optimizing the microstructure and mechanics of pipeline steel welds could further improve the safety and reliability of pipeline operation. In this paper, the effects of single quenching and tempering (single Q-T) and double quenching and tempering (double Q-T) induction heat treatment processes on the microstructure, mechanical properties and damage mechanism of the welds were investigated. The scanning electron microscope (SEM), electron back scatter diffraction (EBSD), and impact tester were used. The results show that single Q-T sample has a smaller grain size hard phase, while there was a smaller grain size and a larger proportion of high angle grain boundary (HAGB) in double Q-T sample. The microhardness of the welded sample, single Q-T sample and double Q-T sample were 222.6 HV5, 247.2 HV5 and 214.8 HV5, respectively. And the impact energy of welded sample, single Q-T sample and double Q-T sample was 57.5 J, 137.7 J and 151.7 J at - 40 °C, respectively. Therefore, the single Q-T process can improve the strength and toughness of the weld metal at the same time, while the double Q-T process can significantly improve the toughness of the weld metal, with slight damage to the strength.